Idea of the ecological and geological tourist centre in Starunia (Fore-Carpathian region, Ukraine) - Adamenko, Oleg M.; Stelmakh, Orest R.; Zorin, Denis O.; Radlovska, Katya O. (Geotourism/Geoturystyka, 2025)
In Starunia village ozokerite deposit was mined in the years 1868-1960. In 1907 remnants of woolly rhinoceros and mammoth were discovered in one of the shafts. A second discovery was made in 1929, in a special shaft digged by the Polish Academy of Arts and Sciences, where remnants of three woolly rhinoceroses were found including one, a unique in the world, almost completely preserved specimen of this extinct species. In the 1970s, mud volcanoes were formed in relationship to seismic activity. In the vicinity of Starunia Paleolithic settlements were found of human population which might have inhabitated this area in the same period as large mammals. Geological, palaeontological and archaeological factors along with beautiful landscape of the Ukrainian Carpathian region make the Starunia village exceptional, world-class geotourist attraction. Hence, the concept of ecological and geological tourist centre has been proposed, located at the abandoned ozokerite mine in Starunia village.